p53 Regulation of Metabolic Pathways - Gottlieb, Eyal (Cold Spring Harbor Laboratory Press, 2010)
During the course of tumorigenesis, cells acquire a number of alterations that contribute to the acquisition of the malignant phenotype, allowing them to survive and flourish in increasingly hostile environments. Cancer cells can be characterized by perturbations in the control of cell proliferation and growth, resistance to death, and alterations in their interactions with the microenvironment. Underpinning many of these changes are shifts in metabolism that allow cancer cells to use alternative pathways for energy production and building the macromolecules necessary for growth, as well as regulating the generation of signaling molecules such as reactive oxygen species (ROS). In the past few years, it became clear that p53, the most studied, if not most important, tumor suppressor protein, can also directly control metabolic traits of cells.